Perancangan Sistem Pengelolaan Limbah Ternak di Cimuncang, Kota Serang - Desta Syaharani, Alifhia; Perdananda, Lingga; Safitri, Salsabila; Sahrupi (Metode : Jurnal Teknik Industri, 2024)
Livestock farming has become a crucial part in meeting the needs of food, industry, and local communities. However, the negative impacts of livestock farming practices, such as improper waste disposal, have led to serious environmental pollution issues. The management of animal waste is key to maintaining environmental cleanliness and livestock health. This research aims to understand strategies for effective and environmentally friendly waste management on farms in the city of Serang. Qualitative methods were employed, including direct interviews with local communities and livestock owners, as well as observations of animal waste storage. Managing animal waste is a crucial task that all farmers must undertake to prevent environmental pollution due to unpleasant odors and the significant negative impact of large quantities of animal waste on crops. It is important to process animal waste before handling or using it as feed. Therefore, this research emphasizes the use of Causal Loop Diagrams (CLD) as a tool to understand and explain waste management in cattle and sheep, based on the research findings presented by the CLD. The modeling results indicate that observations of livestock waste management reveal the presence of 8 internal and external factors influencing this process. These factors are interpreted as variables without fixed values but demonstrating specific behavioral patterns. Identifying these variables can serve as a basis for developing more effective strategies in livestock waste management by understanding and managing the behavioral patterns associated with each variable.